Literature Teaching and the LMD: Learning by Reading - Ould Cheikh Naziad (IJRDO- Journal of Educational Research, 2019)
We could have literature without writing, and we could even have literature without speech but we could not have literature without language. Language is a complex phenomenon and an area of research for the linguist. Literature teachers have seen little need for research on the teaching of literature, while language teachers have investigated language teaching perspectives. The language found in literary texts is particularly interesting for language learners.